REFORMASI HUKUM KEPAILITAN TERHADAP KOPERASI: PEMBATASAN PERMOHONAN PAILIT TERHADAP KOPERASI OLEH ANGGOTA - Aditya Fadhil Avisena; Dhea Ranissya Diza Liestiara (Jurnal Legislatif, 2022)
Bankruptcy petitions by cooperative members have increased since the Covid-19 pandemic. Thisphenomenon raises critics over the disregard for the principle of kinship and the urgency for thegovernment to establish a medium that has the authority to file bankruptcy petitions against cooperatives.This research is structured with juridical-normative research methods along with conceptual approach.This research aims to provide solutions for the government in answering the current issue regardingcooperatives' bankruptcy petitions by its members. Cooperatives have become a place for society to savemoney, even in practice cooperatives are often used as a place to invest. In this regard, cooperatives areimportant entities to be maintained because their existence involves public interests. Thus, it is necessaryto attribute authority to the Ministry of Cooperatives and Small and Medium Enterprises to become themedium in terms of filing bankruptcy petitions against cooperatives. The attribution should be containedin the law on bankruptcy and postponement of debt repayment obligations as well as the law oncooperatives which should be drafted in the future by the government together with the House ofRepresentatives so that there is a guarantee of fresh air in the cooperative sector in Indonesia.